2018
DOI: 10.1371/journal.pone.0203878
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic kidney disease (CKD) patients are exposed to more proton pump inhibitor (PPI)s compared to non-CKD patients

Abstract: BackgroundProton pump inhibitor use is associated with incident chronic kidney disease, chronic kidney disease progression and end-stage renal disease. However, the extent of proton pump inhibitor prescriptions to chronic kidney disease patients is still unclear.MethodIn a retrospective study, we enrolled patients (>18 years old) who received proton pump inhibitor in the out-patient setting from 2014 through 2015. All data was obtained from electronical medical records of Soonchunhyang Medical Center. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 25 publications
2
25
0
1
Order By: Relevance
“…It is nearly similar to Lee et al who observed 7.1% patients with CKD stage 3-4 and 6.6% pts with CKD-5 end stage renal diseases ware using NSAIDs. 15 Santra et al also found that 58% patients were on AMA while 30% patients were on NSAIDs, this is very high as compared with our study. But there are very less studies on the drug utilization in chronic kidney disease patients.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It is nearly similar to Lee et al who observed 7.1% patients with CKD stage 3-4 and 6.6% pts with CKD-5 end stage renal diseases ware using NSAIDs. 15 Santra et al also found that 58% patients were on AMA while 30% patients were on NSAIDs, this is very high as compared with our study. But there are very less studies on the drug utilization in chronic kidney disease patients.…”
Section: Discussionsupporting
confidence: 54%
“…13 In study done by Lee et al observed that CKD patients are taking PPI for a much longer duration compared to non-CKD patients (range 63-273 days vs 56-176 days respectively). 15 In another study of Erdem et al patients with haemodialysis were using PPIs for average of 42.5±35 months (range 3-144 months) which is very high. 14 But it may be harmful because by the Sampathkumar et al the average age of PPI induced AIN was 52.5±18 years while duration of PPI consumption before diagnosis of AIN was 1-8 weeks.…”
Section: Discussionmentioning
confidence: 92%
“…Although several studies have shown higher risks of acute kidney injury (AKI) and CKD associated with long‐term PPI use in the general population, 5–9 studies in CKD patients are rare 10 and the impact of PPIs on outcomes in this population is unclear. Several reports suggest that PPIs are prescribed more frequently in patients with than without CKD 11–13 . We hypothesized that long‐term use of PPIs may be a risk factor for AKI and disease progression to end‐stage in CKD patients.…”
Section: Introductionmentioning
confidence: 99%
“…2 The prevalence of PPI use in the chronic kidney disease (CKD) population is likely higher than for patients without CKD because some studies suggest that patients with CKD are prescribed more PPIs and for longer durations than patients without CKD. 3 PPIs are often used for indications and for lengths of time that were never tested or approved by the US Food and Drug Administration (FDA). They are frequently overprescribed, rarely deprescribed, and often initiated inappropriately during hospitalization, and their use is continued for the long term even in the absence of medical indication.…”
Section: Introductionmentioning
confidence: 99%